Analisis Kompilasi Hukum Islam Terhadap Praktik Kawin Turun di Desa Olibu Kec. Paguyaman Pantai Kab. Boalemo - Afriani Firdaus; Muh. Amin Dali; Warsito Kasim (At-Tanwir Law Review, 2026)
This study aimed to analyze the practice of kawin turun in Olibu Village, Paguyaman Pantai District, Boalemo Regency, and to examine its legal implications under the Compilation of Islamic Law (KHI). Kawin turun referred to a customary form of marriage conducted without official registration at the Office of Religious Affairs (KUA) and was not followed by a complete, enduring household life. The practice emerged as a response to out-of-wedlock pregnancy to preserve family honor and satisfy social expectations. The study employed a qualitative approach with a descriptive-analytical method. The findings indicated that kawin turun did not fully satisfy the pillars and conditions for a valid marriage under Islamic law or the state’s positive law. Consequently, the marriage was not legally recognized, legal protection for women and children was weakened, and civil rights—such as maintenance (nafkah), inheritance, and the child’s legal status—became vulnerable. Therefore, more intensive legal education and religious guidance consistent with sharia principles were needed so that the community understood the importance of marriage registration and the cultivation of marriages characterized by sakinah, mawaddah, and rahmah.Keywords: kawin turun; Compilation of Islamic Law; customary law; marriage; Gorontalo.